Evolution of information and management architectures of higher educational institutions in conditions of disintegration - Danich, V. N.; Shevchenko , S. N. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The article describes features and principles of operation of higher education institutions mostly in Donetsk and Lugansk regions, in conditions of fighting and disintegration territories. The problems of higher education, their solutions de facto and de jure, especially the educational process during the war are analized. There are given examples of administrative decisions regarding university leadership to overcome danger arising from military and political crisis. The main attention is paid to the ways of management and information architecture of higher education institutions in terms of disintegration influence of the political situation and terrorist threats on the work in higher education. There were analysed institutional peculiarities of the split higher educational establishments, problems of implementation of educational process and the conditions affecting the university separation. There were outlined the problems of using distance learning. In the article there are described government regulations that affect the development of information management architecture of universities, it is conducted their analysis. These documents are the following: the concept of strategic development of the university, the strategy of national security, military doctrine, the Law of Ukraine "The grounds of  National Security of Ukraine" and the strategy or plan of institutions of the Ministry of Education, strategic plan for businesses, institutions of certain areas in case of invasion. It was also defined the hierarchy of government regulations and their role in ensuring quality of management decisions concerning the transformation of information management architecture of universities. Also there are singled out key points of such documents.